Effect of alloying elements (Ni and Cr) on density and hardness of Co alloy fabricated by powder metallurgy - Raudhah, Othman; Shamsul Baharin, Jamaludin; Mohd Nazree, Derman (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.